Improved charge carrier transport in ultrathin poly(3-hexylthiophene) films via solution aggregation. Issue 48 (28th November 2016) - Janasz, Lukasz; Chlebosz, Dorota; Gradzka, Marzena; Zajaczkowski, Wojciech; Marszalek, Tomasz; Müllen, Klaus; Ulanski, Jacek; Kiersnowski, Adam; Pisula, Wojciech
Abstract : Field-effect transistors based on poly(3-hexylthiophene) (P3HT) ultrathin films exhibit maximum charge carrier mobilities of up to 0.1 cm 2 V −1 s −1 . Abstract : Field-effect transistors based on poly(3-hexylthiophene) (P3HT) bulk films exhibit maximum charge carrier mobilities of up to 0.1 cm 2 V −1 s −1 . However, reducing the thickness of the polymer film beyond 10 nm results in a significant deterioration of the charge transporting properties. In our work, we demonstrate a strategy towards ultrathin ( i.e. thinner than 10 nm) polymer layers with charge carrier mobilities identical to bulk films. The improvement in conduction is related to aggregation of P3HT in solution allowing the formation of fibrils in the ultrathin films. Changing the molar mass of P3HT as well as varying the solvent type, aging time, and spin coating parameters resulted in layers with different thicknesses and fibrillar microstructures. The crystal packing and microstructure of the P3HT films, studied by atomic force microscopy and X-ray diffraction, were correlated with the transistor performance. It has been found that P3HT nanofibrils serve in the ultrathin films as pathways for charge carriers. Films of 8 nm thickness revealing a high density and a sufficient length of nanofibrils, along with pronounced internal crystallinity and long π-stacking coherence length, yield a mobility of 0.1 cm 2 V −1 s −1 . In this way, we demonstrated that controlling the microstructure of the active film in the ultrathin regime does not have to be at the expense of charge carrier mobility.